The Extended Clinical Phenotype of 58 Patients with Dock8 Deficiency - Engelhardt, K. R.; Gertz, E. M.; Schaeffer, A. A.; Keles, S.; Sigmund, E. C.; Ceja, R.; Grimbacher, B. (Springer/Plenum Publishers, 2014)
[Abstract Not Available]
16th Biennial Meeting of the European-Society-for-Immunodeficiencies -- OCT 29-NOV 01, 2014 -- Prague, CZECH REPUBLIC